Between unjust suffering and the "silent" God: Job and HIV/AIDS sufferers in South Africa - Masenya, Madipoane J. (Missionalia: Southern African Journal of Mission Studies, 2001)
The South African context has historically, at least since the missionary era, been conspicuously shaped by the Christian faith, and more importantly for the present article, also by the Christian Bible. This context also shares a world view that is in many respects similar to that found in the Old Testament. When confronted by the HIV/AIDS pandemic, a devout reader of the Book of Job in the Hebrew Bible cannot remain unchanged. Informed by this (South) African context, how does one make sense of the 'unjust' suffering of the devout biblical character, Job?
Free